The impact of internet use on the subjective age of older adults: evidence and mechanisms - Kong, Zeyu; Zhu, Anqin (Frontiers in Public Health, 2025)
BackgroundIn the context of digitalization and population aging, leveraging Internet technology to reduce the subjective age of older adults helps to promote active aging and healthy aging, thereby contributing to the realization of the development of high-quality national undertakings for the aged.MethodsData from the Chinese Longitudinal Aging Social Survey (CLASS) in 2020 were analyzed. Regression analyses and instrumental variable methods were employed to examine the main effects, heterogeneous effects, and mechanisms of Internet use on the subjective age of older adults. Latent class models and multinomial treatment effect models were used to explore the impact of Internet use patterns on the subjective age of older adults.ResultsInternet use has a significant negative effect on the subjective age of older adults. This conclusion still holds after ruling out endogeneity using instrumental variables methods and conducting various robustness tests. The mechanism test shows that Internet use lowers subjective age by improving health status, self-efficacy, and social capital. Heterogeneity analysis demonstrates that the impact of Internet use on reducing subjective age is more significant among young-old individuals, those with non-agricultural hukou, and those in better economic conditions. Further analysis suggests that different Internet use patterns have varying effects on the subjective age of older adults.ConclusionThis research suggests that Internet use reduces subjective age among older adults. This effect is primarily realized through improvements in health, self-efficacy, and social capital and varies by age, hukou, economic conditions, and Internet use patterns. These findings contribute to the theoretical understanding of how Internet use can delay subjective aging and offer policy implications for enhancing the digital dividend for older adults.